2016
DOI: 10.1051/epjconf/201611604009
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of astrophysical neutrinos observed by IceCube experiment by setting Galactic and extra-Galactic spectral components

Abstract: Abstract. The last IceCube catalog of High Energy Starting Events (HESE) obtained with a livetime of 1347 days comprises 54 neutrino events equally-distributed between the three families with energies between 25 TeV and few PeVs. Considering the homogeneous flavors distribution (1:1:1) and the spectral features of these neutrinos the IceCube collaboration claims the astrophysical origin of these events with more than 5 . The spatial distribution of cited events does not show a clear correlation with known astr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…An alternative method to scans is to use information about the shape of the Galaxy and information about specific Galactic sources to avoid penalty factors. Some approaches have been to consider contributions from Galactic cosmic rays, constraints from gamma rays measured by Fermi, neutrinos from the Galactic center, various Galactic catalogs such as pulsars, pulsar wind nebulae, supernova remnants, decay/absorption from the dark matter JCAP08(2017)033 halo, the Cygnus-X region, bright nearby stars, and even exoplanets [8,12,13,20,22,[26][27][28][29][30][31][32][33]. In all cases it was found that a single Galactic component cannot explain the entirety of the astrophysical flux.…”
Section: Jcap08(2017)033mentioning
confidence: 99%
“…An alternative method to scans is to use information about the shape of the Galaxy and information about specific Galactic sources to avoid penalty factors. Some approaches have been to consider contributions from Galactic cosmic rays, constraints from gamma rays measured by Fermi, neutrinos from the Galactic center, various Galactic catalogs such as pulsars, pulsar wind nebulae, supernova remnants, decay/absorption from the dark matter JCAP08(2017)033 halo, the Cygnus-X region, bright nearby stars, and even exoplanets [8,12,13,20,22,[26][27][28][29][30][31][32][33]. In all cases it was found that a single Galactic component cannot explain the entirety of the astrophysical flux.…”
Section: Jcap08(2017)033mentioning
confidence: 99%
“…Another one comes from the position of the Milky Way. As its central region is at negative declinations, the sum of a Galactic and an extragalactic component [20,21] can result in different spectral behaviours in the two hemispheres. From a statistical point of view, 50% of the observed IceCube cosmic neutrino signal events are compatible with a Galactic plane origin [22].…”
Section: Introductionmentioning
confidence: 99%
“…These issues have led us to question the single power-law hypothesis (1.1) and instead entertain the possibility of a break in the neutrino spectrum [32][33][34][35][36][37][38][39], analogous to (and may be corresponding to [39][40][41][42][43]) the break in the CR spectrum [44]. A two-component flux can arise either from (a) purely astrophysical sources, such as one galactic and one extragalactic component [12,33,39,45,46], or (b) due to a some beyond Standard Model (SM) contribution to the astrophysical neutrino flux, e.g. from heavy dark matter (DM) decay [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%